Reforming Deelneming Doctrine in State Financial Loss Crimes - Bambang Sugeng Rukmono; Roberth Jimmy Lambila; Yessentemirova Aigul Maratovna (Jurnal Justice Dialectical, 2025)
Corruption involving state financial losses remains prevalent in Indonesia, often exacerbated by the ambiguity and divergent interpretations of legal norms, particularly the doctrine of deelneming (criminal participation). The inconsistent and politically influenced application of this doctrine has contributed to legal uncertainty in corruption prosecutions. This study aims to reconstruct deelneming in the context of corruption to enhance legal certainty and promote proportional criminal liability. Employing a normative juridical method, it analyzes legal theories, legislation, and judicial decisions. Findings reveal that the application of deelneming—notably under Article 15 of the Corruption Law and the broad interpretation of Articles 2 and 3—is frequently inconsistent and discriminatory, treating all forms of participation uniformly regardless of intent or role. The study proposes a doctrinal reconstruction grounded in intent theory, causality, and tacit cooperation, streamlining participation into medeplegen (co-perpetration), uitlokking (incitement), and medeplichtige (accomplice), while eliminating plegen and doenplegen. This reconceptualization seeks to reframe deelneming as a foundational legal principle rather than a mere procedural tool, ultimately fostering a fairer and more proportionate framework for criminal liability in corruption cases.